2020
DOI: 10.3390/pathogens9110950
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Liver Fibrosis and HIV Viremia among Patients with HIV, HBV, and Tuberculosis in Botswana

Abstract: People with concomitant human immunodeficiency virus (HIV) and tuberculosis (TB) have an increased risk of hepatotoxic reactions due to antiretroviral therapy (ART) and anti-TB therapy (ATT). Concomitant hepatitis B virus (HBV) in these patients may lead to poorer health outcomes. To assess liver enzyme levels and immune response in adults with HIV, HBV, and TB, data from 300 antiretroviral-naïve people living with HIV (PLWHIV) were analyzed. The prevalence of HIV/HBV (cHIV/HBV) and HIV/TB (cHIV/TB) was 28% (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In HIV patients, liver stiffness increases with advanced AIDS stages, peaking at stage C3. For HIV+HBV patients, higher elastography scores were seen across all stages, suggesting HBV co-infection exacerbates liver disease [ 39 , 40 ]. The highest scores in stage A2 suggest a nonlinear relationship between liver stiffness and AIDS stages in co-infected patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In HIV patients, liver stiffness increases with advanced AIDS stages, peaking at stage C3. For HIV+HBV patients, higher elastography scores were seen across all stages, suggesting HBV co-infection exacerbates liver disease [ 39 , 40 ]. The highest scores in stage A2 suggest a nonlinear relationship between liver stiffness and AIDS stages in co-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…HIV can impair the immune system, making it more difficult to respond to HBV infection and potentially increasing the risk of chronicity. Both viruses can directly affect liver cells, with HIV enhancing fibrogenesis and HBV leading to cell death and regeneration in chronic infections [ 39 ]. Some antiretroviral drugs used to treat HIV have hepatotoxic potential and may cause more damage to the liver in the presence of HBV [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported HBV prevalence and drug resistance mutations among different populations in Botswana [6,[28][29][30][31][32][33][34], but no study has determined the prevalence of HCC-associated HBV mutations in HBV/HIV co-infection. Therefore, we sought to determine the prevalence of the known HCC-associated mutations among HBV/HIV co-infected individuals in Botswana, as well as their association with markers of HBV disease progression.…”
Section: Introductionmentioning
confidence: 99%